Smartphone addiction in COVID-19 pandemic times: a longitudinal study with brazilian dental students - Citó, Erika Brasil Cavalcante; Gondim, Delane Viana; Freire Júnior, Jorge Luiz Moreira; Damasceno, Patrícia Silveira; Oliveira, Maria Caroline Sousa Queiroz Pereira de; Teixeira, Ana Karine Macedo (Revista da ABENO, 2022)
This study aimed to evaluate smartphone addiction, sleep quality, quality of life and depression among dental students before and during the first wave COVID-19 pandemic lockdown and explore how smartphone addiction influences the other variables. 57 dental students answered the smartphone addiction inventory, Pittsburg sleep quality index, WHOQOL-bref and research diagnosis criteria for temporomandibular disorders axis II questionnaires before and during lockdown. Statistical analysis was conducted using Wilcoxon test, Mann-Whitney U test, Spearman tests and linear regression models considering the smartphone addiction inventory total score as the independent variable. The high mean scores on smartphone addiction on both times are remarkable. The smartphone addiction prevalence was also high on both times (68.66% and 71.92% respectively). Overall sleep quality improved. However, there was no significant change on overall smartphone addiction, quality of life and depression grade during lockdown. Tolerance using smartphones increased during lockdown, especially for women. Smartphone addiction showed negative correlation to quality of life and positive correlation to depression, subjective sleep quality and sleep medication use. Smartphone addiction was a predictor to total WHOQOL-bref score, all WHOQOL bref domains, sleep medication use and to depression on both times, before and during lockdown. Smartphone addiction was directly affecting quality of life. Despite the growing smartphone use among university students due to the pandemic restrictions, this study showed that the overall smartphone addiction, quality of life and depression grade were not influenced by the lockdown restrictions. However, it was observed an improvement on sleep quality during this period among dental students.